Análisis del impacto ambiental, generado en los últimos diez años, por las actividades mineras realizadas en el municipio de Sibaté. (2021)
This research work resides in the analysis of the environmental impact generated in the last ten years by the mining activities carried out in the municipality of Sibaté-Cundinamarca, it is characterized by investigating and describing and analyzing the effects on the environmental components given by the processes carried out in the extraction of silica sand and limestone; The exploitation of these materials generates effects on the biotic, abiotic, socioeconomic and cultural components, from the aspect of legal policies, open-pit mining and quarries has a potential impact on environmental components, which is why the Modified qualitative methodology of the national university, for the evaluation of environmental impacts, the results obtained are the characterization and valuation of the potential impacts that are affecting the municipality of Sibaté-Cundinamarca in an environmental, social and cultural way, which compromises environmental resources of current and future generations, in addition to environmental damage as elements of protection in this matter, it is important to highlight the importance of the design of the methodology with which to generate an information system which will be useful for the municipality and any person or entity that wants to know the current state of the municipality io referring to environmental impacts, affected areas, areas of mining projects.